Antioxidant Effect of Ethanol Extract of Bulbus Dayak Onion (Eleutherine americana) to the Quality of Spermatozoa Exposed by Cigarette Smoke in Rats (Rattus norvegicus) - Demes Chornelia Martantiningtyas; Anni Nurliani; Rusmiati Rusmiati (Jurnal Sain Veteriner, 2015)
The toxic substance within the cigarette smoke causing oxidative stress that may damage the quality of spermatozoa. Oxidative stress occurs because the amount of reactive oxygent species and antioxidant produced by the body are not in balanced. One of the alternative approaches of natural antioxidant produced by plant is dayak onion. The bulbus of dayak onion contains steroid, tanin, saphonin, naphtoquinon and flavonoid compound. The aims of this study are to find out the ability of antioxidant from etanol extrat of dayak onion bulbus to increase the quality of spermatozoa affected by smoke and to find out the dose of etanol extrat of dayak onion bulbus that can increase the percentage of viability, morfology, and amount if spermatozoa affected by smoke. In this study, three dose of treatments: 30 mg/kg BW, 60 mg/kg BW, and 90 mg/kb BW were used. The results of dose 30 mg/kg BW, 60 mg/kg BW, and 90 mg/kb BW extended the increased in the normal morfology and amount spermatozoa percentage rather than that of only treated by only the smoke, whereas the viability fordose of 30 mg/kg BW cannot increased in the percentage of spermatozoa viability after affected by smoke.